2015
DOI: 10.1038/ejcn.2015.59
|View full text |Cite
|
Sign up to set email alerts
|

Association between occupational psychosocial factors and waist circumference is modified by diet among men

Abstract: A diet based on the current dietary guidelines seems to cancel out the adverse effects of occupational psychosocial factors on waist circumference among young men. Longitudinal studies are needed to assess the risks for obesity-related diseases arising from psychosocial work environments and dietary habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…However, highest WC and BMI were found to be high in women who occupationally work hard and who are inactive. Our findings came hand in hand with many studies that show an inverse association between BMI, physical activity and occupational activity [2], [15]- [18]. This may be due to the occupational stress that may have a negative impact on individual eating behavior [19]- [21] leading to an increase in body weight and waist circumference accordingly.…”
Section: Discussionsupporting
confidence: 73%
“…However, highest WC and BMI were found to be high in women who occupationally work hard and who are inactive. Our findings came hand in hand with many studies that show an inverse association between BMI, physical activity and occupational activity [2], [15]- [18]. This may be due to the occupational stress that may have a negative impact on individual eating behavior [19]- [21] leading to an increase in body weight and waist circumference accordingly.…”
Section: Discussionsupporting
confidence: 73%
“…Particularly, in men, such work-related factors may strongly influence their daily eating style and food choices, as well as their health condition. Some studies have reported an association between work-related factors and diet in men: job demand/job control and unhealthy diet in relation to waist circumference ( Jaaskelainen et al, 2015 ) and job stress and eating behaviors related to obesity ( Nishitani, Sakakibara, & Akiyama, 2009 ).…”
mentioning
confidence: 99%
“…Brunner et al (2007) and Ishizaki et al (2008) identified that job stress was related to central obesity. Ishizaki et al (2004) and Jääskeläinen et al (2015) observed that the job dimensions were significantly associated with increased WC. In contrast, Garbarino et al (2015) did not verify a significant association between work-related stress and central obesity.…”
Section: Additional Outcomesmentioning
confidence: 96%